A Case of Carbon Monoxide-Induced Delayed Neurological Sequelae Successfully Treated with Hyperbaric Oxygen Therapy, N-Acetylcysteine, and Glucocorticoids: Clinical and Neuroimaging Follow-Up - Vincenzo Spina; Francesco Tomaiuolo; Lorenzo Celli; Luca Bonfiglio; Luca Cecchetti; Maria Chiara Carboncini (Case Reports in Neurological Medicine)
Carbon monoxide (CO) poisoning is a leading cause of intentional and unintentional poisoning worldwide, associated with mortality and severe morbidity. Some survivors of CO poisoning develop, after a lucid interval, a potentially permanent encephalopathy in the form of cognitive impairment and movement disorders, such as Parkinsonism. One of the most frequent neuroimaging findings is a cerebral white matter damage, but so far its precise cause and specific therapy are still debated. We here report the case of a 33-year-old woman with severe carbon monoxide poisoning who, after a period of lucid interval, presented symptoms of declining motor and cognitive functions. She was treated with 40 sessions of Hyperbaric Oxygen Therapy (HBOT). The therapeutic use of oxygen at supraphysiological pressures might either increase systemic oxidative stress or cause an overproduction of oxygen free radicals as drawbacks. Concurrent use of antioxidants and anti-inflammatory drugs may prevent the side effects of oxygen therapy at supraphysiological pressure due to oxidative stress. For this reason, the patient was also treated with high-dose N-Acetylcysteine and glucocorticoids. Here, we describe the longitudinal monitoring of patient’s cognitive abilities and leukoencephalopathy associated with her positive clinical outcome.